SOSIALISASI STRATEGI PEMANFAATAN REPLIKASI BASIS DATA (MASTER-MASTER DAN MASTER-SLAVE) UNTUK PENINGKATAN KINERJA APLIKASI DI RSIA MUTIARA BUNDA - Susilo, Herman; Fauzi, Dede; Ihksan, Muhammad; Abdillah, Nurul (Stikes Syedza Saintika Padang, 2024)
The community service (Pengabmas) event held on February 3, 2024, at RSIA Bunda aimed to enhance application performance by implementing database replication strategies. The event focused on the theme